Fatores determinantes da estrutura de capital das empresas de capital aberto no brasil (1995-2002). - Mendes, Aguinaldo Aparecido (2005)
Abstract The capital structure, comprehended as the financing mix that the firm uses to realize his project, have been largely studied in the last years, because is through the capital structure that the firm will define your success or failure in the future. The purpose of this study was to investigate the determinants factors of capital structure in the Brazilian environment over the period of 1995-2002. The seminal paper of Modigliani and Miller from the beginning of fifties is the turning point of this subject. In this work, the authors affirm that it does not exist an optimal financing mix and the form as the firm is financed is irrelevant. After this point, many different theories were developed with the aim of seeking factors and aspects that affect the capital structure. And consequently, many empirical works were produced on this theme. This study revisits some important theories and empirical works developed on the subject of capital structure. The main purpose of the investigation was to identify some elements that affect the capital structure and to find out how these variables might represent it. The empirical work used factor analysis and regression. An analysis is conducted with the purpose to define the relevant factors to verify the relation between these factors and the level of the debt. Therefore, it was possible to verify some factors that are important to explain the capital structure of open s capital firms in Brazil.